Master techniques in blepharoplasty and periorbital rejuvenation - Massry, Guy G.; Murphy, Mark R.; Azizzadeh, Babak (New York, New York Springer New York, 2011)
The eyes are a central feature of facial appearance, expression and provide us the ability to see, our most important sensory function.  For this reason, mastering the evaluation and execution of aesthetic rejuvenation of the eyelids and adjacent areas is critical to all surgeons who operate on these very delicate and interconnected structures. Master Techniques in Blepharoplasty and Periorbital Rejuvenation is a comprehensive, multi-specialty textbook on blepharoplasty and eyelid reconstruction. Special features include: A multidisciplinary view of how this particular area of facial aesthetic surgery is approached and how its associated procedures are performed; Provides a unique and comprehensive understanding of cosmetic brow lifting, blepahroplasty and midface surgery; Written by leading experts in a variety of specialties, including oculoplastic surgery, facial plastic surgery, plastic surgery and dermatology.
Periorbital Aesthetic Surgery: The Evolution of a Multidisciplinary Surgical Subspecialty -- Surgical Anatomy of the Forehead, Eyelids, and Midface for the Aesthetic Surgeon -- The Beautiful Eye: Perception of Beauty in the Periocular Area -- Critical Evaluation of the Periorbital Aesthetic Patient -- Oculofacial Anesthesia -- The Open Approach to Forehead Lifting -- Endoscopic Brow and Forehead Rejuvenation -- Direct Brow Lift: An Aesthetic Approach -- Upper Eyelid Blepharoplasty -- Adjunctive Procedures in Upper Eyelid Blepharoplasty: Internal Brow Fat Sculpting and Elevation, Glabellar Myectomy, and Lacrimal Gland Repositioning -- Management of Complications of Upper Eyelid Blepharoplasty -- Levator Ptosis Repair in the Aesthetic Patient With and Without Blepharoplasty -- Posterior Approach Ptosis Repair in the Aesthetic Patient With or Without Blepharoplasty -- Modern Advances in Asian Blepharoplasty -- Transcutaneous Lower Eyelid Blepharoplasty -- Transconjunctival Lower Blepharoplasty: Fat Excision or Repositioning -- Managing the Lateral Canthus in the Aesthetic Patient -- Management of the Post-lower Eyelid Blepharoplasty Retracted Eyelid -- Laser Management of Festoons -- Midface and Lower Eyelid Rejuvenation -- Face Implants in Aesthetic Surgery -- Periorbital Fat Grafting -- Periorbital Laser Resurfacing -- Laser Incisional Eyelid Surgery -- Neuromodulators and Fillers for Periorbital Rejuvenation -- Management of the Prominent Eye -- Postoperative Wound Modulation in Aesthetic Eyelid and Periorbital Surgery -- Short-Flap Superficial Musculo-Aponeurotic System (SMAS) Rhytidectomy.
Electronic reproduction.
Keywords: Blepharoplasty -- Technique; Ophthalmic plastic surgery -- Technique